Upaya Hukum Terhadap Rumah Susun yang Tidak Memenuhi Persyaratan Teknis dalam Sertfikat Laik Fungsi - Aripin, Jacqueline (JURNAL MINUTA, 2025)
The scarcity of land has prompted a shift towards vertical housing solutions, with apartments gaining prominence as a viable alternative to traditional single-family dwellings. However, In creating a suitable apartment development, the apartment developer should pay attention to the requirements for the apartment, one of which is contained in the form of Sertifikat Laik Fungsi (SLF) based on Law No. 20 of 2011. SLF essentially functions in providing legality for the operation of an apartment and providing a sense of security. However, in fact there are still flats that have SLF, but they do not comply with the actual condition of the building's reliability, causing losses to the flat's occupants. One of them occurred at the PH Flats. For this reason, the author is interested in studying legal violations regarding SLF ownership by the PH Flats along with the legal measures that can be taken by the residents of the flats due to the losses they suffer. This research is based on normative research methods as well as statutory and conceptual approaches with data sources and types of primary legal materials. The results of this research indicate that legal violations regarding SLF ownership are caused by mal administrative actions by Dinas Cipta Karya dan Tata ruang in issuing SLF along with violations of building reliability requirements carried out by apartment developers. There are legal remedies that can be taken by apartment residents, both in litigation and non-litigation efforts.